Intimate Partner Violence and Risk for Mortality and Incident Dementia in Older Women - Cations, Monica (Journal of interpersonal violence, 2022)
The aim of this study was to assess the long-term risk for mortality and incident dementia associated with exposure to intimate partner violence (IPV) at any time over the life course. Data were taken from the Australian Longitudinal Study of Women?s Health, a population-based cohort study initiated in 1996. Analysis is based on 12,085 community-dwelling women aged 70 to 75 years at baseline from all states and territories. Self-reported exposure to violence was separated into historical (any time before baseline), current (past 12 months), or both. Date of death was obtained from the National Death Index, and dementia status was self-reported or obtained from administrative data. We modeled mortality risk using Cox regression, and risk for incident dementia using Fine-Gray proportional hazards modeling with death as a competing risk. Follow up continued to December 2017. At baseline, 728 women (6.0%) reported historical IPV, 121 (1.0%) reported current violence, and 38 reported both (0.3%). Historical IPV increased 20-year mortality risk after controlling for demographic, socioeconomic, and lifestyle variables (hazard ratio 1.10, 95% confidence interval = [1.00, 1.20]). There was no relationship between current violence and mortality (hazard ratio 1.04, 95% confidence interval = [0.85, 1.29]). There was also no association between IPV and risk for incident dementia (hazard ratio 1.02, 95% confidence interval = [0.89, 1.17]). Older women who self-report exposure to IPV over the lifespan die significantly earlier than women who do not. Further research that considers the mediating role of psychological trauma is needed to examine the relationship between IPV and dementia.